Investigation on UV-A light photocatalytic degradation of an azo dye in the presence of CdO/TiO2 coupled semiconductor. (July 2015) - Dhatshanamurthi, P.; Subash, B.; Shanthi, M.
Abstract: CdO/TiO2 composites were prepared by sonochemically assisted sol–gel method. Initially, CdO was prepared by precipitation-thermal decomposition method and used for composites preparation. The prepared catalysts were used for the degradation of an azo dye, Reactive Orange 4 (RO 4) under UV-A light. 5 wt% CdO/TiO2 composite was found to be very efficient towards RO 4 degradation, this catalyst was characterized by different characterization techniques (XRD, SEM, EDS, TEM, PL and BET surface area measurements) besides bare TiO2 was also characterized for comparison. 5 wt% CdO/TiO2 showed the best photocatalytic activity in the degradation of RO 4 compared with the bare TiO2, TiO2 -P25 and CdO. The effects of operational parameters such as the amount of photocatalyst, initial pH and dye concentration have been analyzed. The mineralization of RO 4 has been confirmed by chemical oxygen demand (COD) measurements. A mechanism has been proposed for the degradation of RO 4 under UV-A light. This catalyst is found to be more stable and reusable.